1983
DOI: 10.1016/0095-8956(83)90056-4
|View full text |Cite
|
Sign up to set email alerts
|

Shortest coverings of graphs with cycles

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 8 publications
1
100
0
1
Order By: Relevance
“…The following result of Alon and Tarsi [1] and Bermond, Jackson and Jaeger [2] is the best known general result on the length of cycle covers.…”
Section: Short Cycle Coversmentioning
confidence: 99%
“…The following result of Alon and Tarsi [1] and Bermond, Jackson and Jaeger [2] is the best known general result on the length of cycle covers.…”
Section: Short Cycle Coversmentioning
confidence: 99%
“…Bermond, Jackson, and Jaeger [1] showed that every 2-edge-connectedgraph has a collection of seven even subgraphs so that every edge is in exactly four of these subgraphs. This easily implies that every 2-edge-connected graph has an 7-dimensional unit distance flow.…”
Section: -Flowmentioning
confidence: 99%
“…We do so by bounding the summation through a product of terms that involves what we call apples-an apple is a simple cycle or a cycle plus a connected line. Along with the result of Bermond, Jackson, and Jaeger [3], this leads to the eventual result that the error in the Bethe approximation for the number of independent sets decays as Oðn −γ Þ for some γ > 0 for any graph on n nodes with max-degree d and girth larger than 8d log 2 n.…”
Section: Our Resultsmentioning
confidence: 99%